Preliminary observation on sexual maturity of black anglerfish (Lophius budegassa) in north-eastern Atlantic waters - Landa, Jorge; Antolínez, Ana; Ámez, Marco Antonio; Barrado-Fernández, Joaquín; Castro-Loehmann, Begoña; Cañás, Lucía; Autón-Díaz, Urbano Ramón; Fariña-Pérez, Celso; Hernández, Carmen (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)
The reproduction of black anglerfish (Lophius budegassa) was studied from samples collected during 5 years, from January 2006 to December 2010, in Celtic Sea, West and South of Ireland (ICES Div. VIIb–k) and Northern Spanish Atlantic waters (ICES Div. VIIIc–IXa). A total of 1167 specimens (4–99 cm) were sampled. The sex ratio, the spawning period and the maturity ogives by length were studied. The sex ratio in both areas studied varied with length, and it was close to 1:1 (male:female), 1:1.22 (54.90% of females) in Div. VIIb–k, and 1:1.01 (50.30% of females) in Div. VIIIc–IXa. A seasonal variation in sex ratio by length was observed at first time in Div VIIIc–IXa, with a very low proportion of intermediate sized females (40–60 cm) in the second semester. A seasonal reproductive migratory behavior is discussed. The spawning period was between December and July in Div. VIIIc–IXa. Spawning males were found throughout the year, but fewer spawning females, as in previous studies. The L50 values were estimated in Div. VIIIc–IXa: 38.2 cm for combined sexes, 36.0 cm for males and 53.0 cm for females. These values of sex ratio and L50 are similar to those obtained in closed areas studied.